2020
DOI: 10.1001/jama.2020.6627
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Risks Posed to Personnel During Endotracheal Intubation

Abstract: Health care personnel who care for critically ill patients with suspected or confirmed novel coronavirus disease 2019 (COVID-19) routinely participate in procedures, such as endotracheal intubation, that may create infectious aerosols. Among persons infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19, approximately 8% will require endotracheal intubation and mechanical ventilation. 1 Aerosol-generating procedures have been described as "…procedures perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
154
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 8 publications
0
154
0
3
Order By: Relevance
“…Proceeding with such surgeries puts the patient and staff at risk for viral transmission, especially during endotracheal intubation and extubation. 11 In the event of repeated recommendations for the cessation of elective surgery, aesthetic procedures may still be offered in outpatient centers without overnight stays.…”
Section: Discussionmentioning
confidence: 99%
“…Proceeding with such surgeries puts the patient and staff at risk for viral transmission, especially during endotracheal intubation and extubation. 11 In the event of repeated recommendations for the cessation of elective surgery, aesthetic procedures may still be offered in outpatient centers without overnight stays.…”
Section: Discussionmentioning
confidence: 99%
“…At our centers, our overarching goal was to minimize airway manipulation and aerosol generation. Others might reasonably prioritize avoidance of hypoxemia, and so might prefer methods such as endotracheal intubation, supraglottic airway placement, high flow nasal cannula, or non-invasive ventilation, which provide more reliable oxygen delivery at the cost of additional aerosol generation [28-30]. As present evidence is uncertain about the relative aerosol risk of BMV versus these interventions, any may be reasonable to use particularly for subsequent treatments of patients who desaturate with the procedure described here.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…According to recent guidelines, tracheostomy is not recommended because of the high risk of virus aerosolization to healthcare workers, and transmission through health care facilities [13]. There is the same potential risk for the endotracheal intubation, as a hazardous and high-risk aerosol-generating procedure [14]. A meta-analysis and systematic review reported the risk of this transmission to the medical staff for SARS-CoV-1 infection, with a signi cantly increased the odds ratio (OD) of 6.6 [8].…”
Section: Discussionmentioning
confidence: 99%